Influência do molibdênio e do cálcio aplicados via semente nas frações protéicas de amendoim cv.iac 886 - da Silva, Mariana Pina [UNESP]; de Sa, Marco Eustaquio [UNESP]; Abrantes, Fabiana Lima [UNESP]; Domingues de Souza, Lilian Christian [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Chemical composition of seed displays, in general, the same compounds found in other parts of the plant, and the environment where they grow plants, fertilizer and many other factors are able to change this constitution, increasing or decreasing the amount of certain components. The study aimed to determine the effect of application by seed doses of calcium and molybdenum on protein content of peanut seeds cv.IAC 886. The experimental design was randomized blocks in a factorial design with four replicates per treatment, which are constituted by the combination of molybdenum doses (0, 50, 100 and 150 g ha(-1)) and calcium by seeds (0, 1000, 2000 and 3000 mg L-1). The peanut harvest was done manually. Seeds were removed from the pod manually and individually for each treatment and were taken to the Laboratorio de Genetica de Populacoes e Silvicultura, do Departamento de Fitotecnia, Tecnologia de Alimentos e Socio-Economia, da Faculdade de Engenharia de Ilha Solteira da Universidade Estadual Paulista, where we determined the protein (albumin-Alb, prolamin-PRO, glutelin-GLU and globulin-GLO, mg g(-1). Regardless of the doses used the albumin protein fraction showed the highest in the peanut seeds. The addition of molybdenum resulted in increased seed prolamin content in the peanut seeds. The combination of calcium and molybdenum applied to seeds resulted in increased levels of albumin, globulin and glutelin in the peanut seeds.
Influence of molybdenum and calcium applied to seeds in peanut protein fractions cv.IAC 886
Keywords: Albumin; prolamin; glutelin and globulin